Masking the Perceived Astringency of Proanthocyanidins in Beverages Using Oxidized Starch Hydrogel Microencapsulation - Xiaodan Zhao; Yingchao Ai; Yulin Hu; Yongtao Wang; Liang Zhao; Dong Yang; Fang Chen; Xiaomeng Wu; Yuan Li; Xiaojun Liao (Foods, 2020)
Proanthocyanidins (PAs) are responsible for several health benefits of many fruits, but they could cause a generally disliked sensation of astringency. Traditional deastringency methods remove bioactive ingredients, resulting in the loss of valuable nutrients and associated health benefits. This work aimed to microencapsulate PAs from grape seeds using oxidized starch hydrogel (OSH) and mask its perceived astringency in beverages while maintaining its bioavailability. The maximum PA uptake capabilities of OSH, as well as the binding site and primary binding force between these two components, were determined. The resulting PA-OSH complex was stable under in vitro digestion, with only 1.6% of PA being released in the salivary digestion, and it has an intestine-specific release property. The reaction of PA with α-amylase in artificial saliva was substantially reduced by OSH microencapsulation, leading to 41.5% less precipitation of the salivary proteins. The sensory evaluation results showed that the microencapsulation was able to mask the astringency of PA-fortified water, as the perceived threshold of astringency increased by 3.85 times. These results proved that OSH could be used as a novel food additive to reduce the astringency of beverage products due to its hydrogel properties and ability to encapsulate phenolic compounds.